Increasing antepartum Tdap vaccine administration: A quality improvement initiative. Issue 28 (19th June 2019) - Jina, Asmita; Wang, Tiffany L.; Seyferth, Elisabeth R.; Cohen, Amy; Bernstein, Henry H.
Abstract: The Centers for Disease Control and Prevention (CDC) recommends antepartum Tdap vaccination for women with each pregnancy to protect themselves and their vulnerable infants through transplacental transfer of maternal antibodies. Our aim was to increase the rate of antepartum Tdap vaccine administration by 20%. Obstetricians were surveyed to identify their present approaches and barriers to antepartum Tdap vaccine administration to help guide the development of our intervention. Limited staff training, lack of vaccine on site, and cost were the most commonly identified barriers. Using these survey responses, existing literature, and brainstorming conversations with colleagues, an interdisciplinary workgroup then created a fishbone analysis and developed a 5-step intervention to address these barriers: (1) educate providers and patients on Tdap and pertussis; (2) increase Tdap availability to all pregnant women; (3) remind staff of the established Tdap standing order to facilitate administration; (4) encourage obstetricians to offer Tdap; (5) transfer documentation of Tdap administration from office to hospital. To monitor changes in the process over 15 months of pre- and post-intervention, data were collected from monthly chart audits and a two-phase control chart was created. The main outcome measure was proportion of eligible women who received Tdap during current pregnancy. In the pre-intervention period, 362 of 636 eligible women (56.9%) received Tdap during their current pregnancy; in the post-intervention period, 457 of 708 eligible women (64.5%) received Tdap during their current pregnancy. This absolute difference of 7.6% (64.5% vs. 56.9%, p < 0.01) represents a 13.4% relative increase (64.5%/56.9%) in the proportion of clinically eligible pregnant women who received Tdap. This represents a clinically and statistically significant increase in the rate of antepartum Tdap immunization. More research is needed to further understand obstetric barriers and maternal refusal of antepartum Tdap administration.